Peran Guru Pendidikan Agama Kristen (PAK) Dalam Implementasi Pembelajaran Interaktif Berbasis Teknologi Untuk Meningkatkan Motivasi Belajar Siswa - Anarasian A. Rapa; Dyulius Thomas Bilo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Technology-enhanced interactive learning in Christian religious education holds great potential for enhancing students' learning motivation and understanding of Christian values. This article discusses the crucial role of Christian Religious Education (CRE) teachers in designing and implementing this approach, as well as the challenges encountered in the process. Interactive learning leverages tools and platforms such as Classpoint, Slido, and other applications to create a dynamic and contemporary learning environment. Teachers are tasked with selecting and adapting Christian religious content that meets students' needs while utilizing interactive features to enhance student engagement. Challenges including limited technology access, inadequate technological skills, and resistance to change are also addressed within the context of technology integration in religious education. By combining technological innovation with appropriate pedagogical approaches, teachers can maximize the potential of interactive learning to create meaningful and effective learning experiences that deepen students' understanding and application of Christian values in everyday life.